Waiting for the doctor to ask: influencers of lesbian, gay, and bisexual identity disclosure to healthcare providers - Nicole C. Hudak; Heather J. Carmack (Qualitative Research in Medicine & Healthcare)
Lesbian, gay, and bisexual (LGB) individuals encounter multiple barriers in healthcare, resulting in problematic care. Many LGB patients wrestle with whether to disclose their sexuality to healthcare providers. This article explored what influences LGB patients’ decision to disclose their sexuality to healthcare providers. Guided by Communication Privacy Management theory, the authors conducted in-depth interviews with 20 LGB patients. LGB patients heavily relied on boundary management when negotiating the disclosure of their sexuality. The findings suggest several factors influence LGB patients’ disclosure of sexuality: i) experience with family; ii) fear of gossip and connections; iii) concern for provider care refusal; iv) religion; v) age; and vi) level of trust with providers. Boundary turbulence can be created between patient and provider when there is uncertainty about if and when sexuality is considered private information. Additionally, a site of tension for LGB patients was their concern about providers sharing private information outside the clinic setting.